Pengembangan minuman fungsional berbasis bubuk kakao lokal berkualitas tinggi dengan penambahan madu: analisis sifat fisik, kimia, dan umur simpan - Risma, Risma; Kusnandar, Feri; Herawati, Dian; Adalina, Yelin (AGROINTEK, 2025)
This study aims to evaluate the effects of combining cocoa bean extract and honey in a functional beverage formulation, focusing on physical, chemical, and antioxidant properties. Cocoa beans used were of the Sulawesi 2 clone, sourced from Donggala, Palu, while honey was sourced from Sumbawa, East Nusa Tenggara. The research methods included analysis of total phenolics, flavonoids, catechin, epicatechin, theobromine, and caffeine content using HPLC, and antioxidant activity was assessed using the DPPH method. The functional beverage was formulated by mixing cocoa powder and honey in various doses, pasteurized at 75°C, and stored at 8-10°C. The addition of honey influenced the phenolic content and antioxidant effectiveness in formulations F1 and F2. Formulation F2 (10.17% cocoa powder, 8.47% honey, and 81.36% water) showed a total phenolic content of 9.36 mg GAE/g. Meanwhile, formulation F1 (10.34% cocoa powder, 6.90% honey, and 82.76% water) had a lower total phenolic content of 6.60 mg GAE/g. Although total phenolics and antioxidant activity decreased due to pasteurization and brewing, F2 (DPPH value of 0.30 mg TEAC/g) demonstrated higher antioxidant activity than F1 (DPPH value of 0.14 mg TEAC/g). Statistical analysis revealed significant differences in total phenolic content and pH between F1 and F2 (p 0.05). However, no significant differences were observed in antioxidant activity (p 0.05). Therefore, it is essential to consider processing methods to maintain the antioxidant activity of cocoa products derived from the Sulawesi 2 clone.